Answer: The simplified expression is: " 100x - 100 . "
____________________________________________________
Step-by-step explanation:
____________________________________________________
Step 1) Choose a number; Let this number be represented by: " x " .
____________________________________________________
Step 2) Multiply "x" by " (-11) " ; as follows:
x * (-11) = -11 * x = - 11x .
____________________________________________________
Step 3) Add "5" to: " -11x " ; as follows:
5 + (-11x) = -11x + 5 .
____________________________________________________
Step 4) Multiply: " (-11x + 5) by: " (-9)" ; as follows:
-9(-11x + 5) = ?
____________________________________________________
Note the "distributive property" of multiplication:
a(b + c) = ab + ac .
____________________________________________________
As such:
-9(-11x + 5) =
(-9 * -11x) + (-9 * 5) =
99x + (-45) =
99x - 45 .
____________________________________________________
Step 5: Add "x" to: " (99x - 45) " ; as follows:
99x - 45 + x =
99x + x - 45 =
100x - 45 .
____________________________________________________
Step 6: Subtract "55" from: " (100x - 45) " ; as follows:
100x - 45 - 55 = ?
- 45 - 55 = - 100 ;
100x - 45 - 55 =
100x - 100 .
or: Factor out a "100" ;
→ 100 (x - 1) ;
However, the simplified expression is: " 100x - 100 " .
____________________________________________________